Aluminum doping for optimization of ultrathin and high-k dielectric layer based on SrTiO3 - Baek, Ji Ye; Duy, Le Thai; Lee, Sang Yeon; Seo, Hyungtak (Journal of Materials Science and Technology, 2020)
An ultrathin SrTiO3 dielectric layer is optimized through Al doping to solve the problems existing in development of ultra-high-k oxide MOS capacitors. Through post-deposition annealing, Al doping induces changes in the electronic structure of SrTiO3, thereby effectively reducing leakage current to <10−8 A/cm2 at 0.5 MV/cm but maintains good capacitance values (ε > 80) of ultrathin SrTiO3 MOS capacitors. Strontium titanate (SrTiO3) is a high-k material but its bandgap is smaller than that of other oxide dielectrics (e.g., SiO2, Al2O3). Consequently, an ultrathin SrTiO3 film may have a high tunneling leakage current, which is not suitable for capacitor-based applications. To improve the performance of metal–oxide–semiconductor (MOS) capacitors using SrTiO3, an approach based on homogenous and uniform aluminum doping to SrTiO3 through co-sputtering is introduced. The bandgap of a pristine SrTiO3 film showed an increase of 0.5 eV after Al doping. Furthermore, Al doping decreased the leakage current of SrTiO3/Si-based MOS capacitors by more than five orders of magnitude (at the level of nanoampere per square centimeter). Importantly, a dielectric constant of 81.3 and equivalent oxide thickness less than 5 Å were achieved in an 8-nm-thick Al-doped SrTiO3 film owing to changes in its crystal structure and conduction band edge electronic structure. Thus, the obtained data show the effectiveness of the proposed approach for solving the problems existing in the development of ultra-high-k oxide MOS capacitors.
Keywords: Aluminum doping; Equivalent oxide thickness; High dielectric constants; High-k dielectric layers; Post deposition annealing; SrTiO3; Tunneling leakage current; Ultra-thin; Aluminum doping; High dielectric constant; MOS capacitors; SrTiO3; ultrathin